Knockdown of carnitine palmitoyltransferase I (CPT1) reduces fat body lipid mobilization and resistance to starvation in the insect vector Rhodnius prolixus - De Paula, Iron F.; Santos-Araujo, Samara; Majerowicz, David; Ramos, Isabela; Gondim, Katia C. (Frontiers in Physiology, 2023)
The energy stored in fatty acids is essential for several critical activities of insects, such as embryogenesis, oviposition, and flight. Rhodnius prolixus is an obligatory hematophagous hemipteran and vector of Chagas disease, and it feeds infrequently on very large blood meals. As digestion slowly occurs, lipids are synthesized and accumulate in the fat body, mainly as triacylglycerol, in lipid droplets. Between feeding bouts, proper mobilization and oxidation of stored lipids are crucial for survival, and released fatty acids are oxidized by mitochondrial β-oxidation. Carnitine palmitoyl transferase I (CPT1) is the enzyme that catalyzes the first reaction of the carnitine shuttle, where the activated fatty acid, acyl-CoA, is converted to acyl-carnitine to be transported into the mitochondria. Here, we investigated the role of CPT1 in lipid metabolism and in resistance to starvation in Rhodnius prolixus. The expression of the CPT1 gene (RhoprCpt1) was determined in the organs of adult females on the fourth day after a blood meal, and the flight muscle showed higher expression levels than the ovary, fat body, and anterior and posterior midgut. RhoprCpt1 expression in the fat body dramatically decreased after feeding, and started to increase again 10 days later, but no changes were observed in the flight muscle. β-oxidation rates were determined in flight muscle and fat body homogenates with the use of 3H-palmitate, and in unfed females, they were higher in the flight muscle. In the fat body, lipid oxidation activity did not show any variation before or at different days after feeding, and was not affected by the presence of etomoxir or malonyl-CoA. We used RNAi and generated RhoprCPT1-deficient insects, which surprisingly did not show a decrease in measured 3H-palmitate oxidation rates. However, the RNAi-knockdown females presented increased amounts of triacylglycerol and larger lipid droplets in the fat body, but not in the flight muscle. When subjected to starvation, these insects had a shorter lifespan. These results indicated that the inhibition of RhoprCpt1 expression compromised lipid mobilization and affected resistance to starvation.